2005
DOI: 10.1002/bio.867
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of antioxidants as quenchers or scavengers of reactive oxygen species based on quenching of MCLA-dependent chemiluminescence

Abstract: The quenching or scavenging effect of non-enzymatic antioxidants against reactive oxygen species (ROS) was studied by comparing the degree of suppression of chemiluminescence (CL) caused by the oxidation of MCLA (methoxylated Cypridina luciferin analogue) by ROS. MCLA-dependent CL caused by O2- was effectively quenched by ascorbic acid, beta-carotene, lycopene and astaxanthin, while it was enhanced by alpha-tocopherol. The CL by 1O2 was quenched effectively by beta-carotene, lycopene and astaxanthin, moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
0
25
0
2
Order By: Relevance
“…Singlet oxygen was generated by light irradiation of a rose Bengal solution in a test tube, and detected by chemiluminescence of MCLA 17,18. The suspension of Asx‐EPC‐lipo (0.1 mL) was diluted with 0.879 mL of deionized distilled water, followed by the addition of 20 µL of 0.5 mM rose Bengal solved with deionized distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Singlet oxygen was generated by light irradiation of a rose Bengal solution in a test tube, and detected by chemiluminescence of MCLA 17,18. The suspension of Asx‐EPC‐lipo (0.1 mL) was diluted with 0.879 mL of deionized distilled water, followed by the addition of 20 µL of 0.5 mM rose Bengal solved with deionized distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…L-Ascorbic acid was purchased from Sigma-Aldrich Japan K.K. (11). Catechin hydrate was purchased from Spectrum Chemical Manufacturing Corp. (Gardena, CA; refs.…”
Section: Methodsmentioning
confidence: 99%
“…The strong CL phenomenon indicated that ROS was released on CaO 2 . In order to acquire sufficient evidence, ascorbic acid, a well-known ROS scavenger (22)(23)(24), was chosen for further experiments. As shown in Fig.…”
Section: Confirmation Of Ros On Cao 2 By CLmentioning
confidence: 99%